Pendekatan Teori Perilaku Berencana Terhadap Minat Beli Produk Ramah Lingkungan - Lady Lady; Susanti Susanti; Hesniati Hesniati (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to link environmental concern and the theory of planned behavior to the intention to purchase green products in Indonesia. Purpose: This study aims to link environmental concerns and the theory of planned behavior to the intention to purchase green products. Methodology/approach: This research was conducted from December 2023 to January 2024 with 359 respondents using convenience sampling method. The research object is the purchaser of green products in Indonesia. Data analysis was performed using partial least squares structural equation modelling (PLS-SEM). Results/findings: The results show that environmental concern significantly and positively affects green attitudes. Green attitude, green behavior control, and green product awareness all had significant positive effects on green purchase intention. Green attitude mediates the effect of environmental concern on the intention to purchase green products. This study found that subjective green norms do not significantly affect green purchase intentions. Conclusions: In Indonesia, green purchase intention is primarily driven by environmental concern, attitude, control, and awareness, while subjective norms have no effect. Community campaigns are needed to strengthen the social influence of eco-friendly consumption. Limitations: The use of convenience sampling method in data collection may lead to the issue that not all participants represent the general population. Additionally, this study did not specifically focus on the use of environmentally friendly products such as electronics, vehicles, or food. Contribution: This study contributes to the literature on green marketing by enhancing the intention to purchase green products among business owners and policymakers. This will raise public awareness of environmental issues in Indonesia. Methodology/approach: This research was conducted from December 2023 to January 2024 with 359 respondents using convenience sampling. Data analysis was performed using partial least square – structural equation modeling (PLS-SEM). Results/findings: The results show that environmental concern has a significant positive effect on green attitude. Green attitude, green behavior control, and green product awareness all have a significant positive effect on green purchase intention. Green attitude mediates the effect of environmental concern on the intention to purchase green products. This study found that green subjective norm does not significantly affect green purchase intention. Limitations: The use of the convenience sampling method in data collection may lead to the issue that not all participants represent the general population. Additionally, this study does not specifically focus on the use of environmentally friendly products, such as electronics, vehicles, or food. Contribution: The results of this study will provide academic contributions by linking environmental concern with the theory of planned behavior (TPB) approach to explore the psychological factors in explaining the intention to purchase green products. Second, it will contribute to business owners and policymakers in enhancing the intention to purchase green products. Third, it will raise awareness among the general public about environmental issues in Indonesia.